(untitled) (Journal of Global Accounting, 2023)
Extremely high exchange rate fluctuations will disrupt economic activity from both the real sector and the monetary sector. The study determines the relationship between exchange rate and the financial performance of oil and gas firms listed in Nigerian Exchange Group, over a period of ten (10) years spanning from 2012 to 2021. Specifically, the study intends to ascertain the extent to which exchange gain (loss) relates to return on capital employed, return on assets and net profit margin. Ex-post facto research design was deployed in the study. Relevant data for the study were obtained from the published financial statements of six (6) sampled listed oil and gas firms on the Nigerian Exchange Group. Ordinary least square regression and robust least square regression analyses were used to test the relevant hypotheses. The findings indicated that: there is a significant and positive relationship between exchange gain (loss) and Returns on Capital Employed of listed oil and gas firms in Nigeria at 5% level of significance; there is a significant and positive relationship between exchange gain (loss) and Return on Asset of listed oil and gas firms in Nigeria at 5% level of significance; there is a significant and positive relationship between exchange gain (loss) and net profit margin of listed oil and gas firms in Nigeria at 5% level of significance. The study concludes that loss of earnings occurs due to a mismatch between the value of assets and that of capital and liabilities denominated in foreign currencies or a mismatch between foreign receivables and foreign payables that are expressed in domestic currency. It was therefore recommended that the government should consider using more resourceful information technology infrastructure to provide information on exchange rates to the wider public in order to improve the information efficiency in the foreign exchange market.